Endothelin receptor blockade does not affect blood pressure or angiotensin II levels in CYP1A1-Ren-2 transgenic rats with acutely induced hypertension - Vanourková, Zdenka; Kramer, Herbert J; Erbanová, Michaela; Bäcker, Angela; Cervenka, Ludek; Husková, Zuzana; Chábová, Vera Certíková; Tesar, Vladimír; Dvorák, Pavel; Malý, Jan; Vanecková, Ivana (Vascular pharmacology, 2009)
We found previously that selective blockade of endothelin ETA receptors is superior to nonselective ET(A)/ET(B) in attenuating hypertension and survival rate in Ren-2 transgenic rats (TGR). In the present pilot study, we were interested in whether similar effects will be found in TGR with inducible malignant hypertension (iTGR; official strain name Cyp1A1-Ren-2rats), which were derived from the original Ren-2 transgenic rat strain. Studies were performed in three-month old male iTGR. Treatment with either bosentan, a non-selective ET(A)/ET(B), or with atrasentan, a selective ET(A) receptor blocker, was started on day 2 of the experiment. Feeding with indole-3-carbinole (13C; 03% in rat chow), a natural xenobiotic which activates the Cyplal promoter of the mouse Ren-2 gene, began on day 3 and lasted for 4 days until day 6. Systolic BP, body weight, plasma ANG II and tissue ANG II and ET-1 concentrations were determined daily. Severe hypertension developed as early as 1 day after beginning of 13C feeding which was accompanied by a significant reduction in body weight and by increases in plasma and tissue ANG II and left ventricle ET-1 concentrations. Atrasentan or bosentan had no effects on the rise in BP or plasma and tissue ANG II concentrations but prevented the rise in heart ventricle ET-1 concentration. Our data show that blockade of the ET system does not prevent or attenuate the rapid development of severe hypertension in iTGR; a long-term protective effect of ET blockade on cardiac (and renal) damage, however, cannot be excluded and awaits further investigations.
Keywords: Endothelin-1; indoly; antagonisté endotelinového receptoru; atrasentan; Cytochrome P-450 CYP1A1; Pyrrolidines; cytochrom P-450 CYP1A1; Indoles; renin; potkani transgenní; Hypertension; ledviny; Angiotensin II; sulfonamidy; angiotensin II; endotelin-1; Kidney; krysa rodu Rattus; bosentan; Antihypertensive Agents; Atrasentan; zvířata; Bosentan; Rats, Transgenic; Endothelin Receptor Antagonists; Renin; krevní tlak; Male; hypertenze; Heart Ventricles; Rats; Animals; antihypertenziva; mužské pohlaví; pyrrolidiny; Blood Pressure; Disease Models, Animal; srdeční komory; Sulfonamides; modely nemocí na zvířatech